L’éthique de la recherche entre réglementation et réflexivité - Sarah Carvallo (Revue d'anthropologie des connaissances)
Over the last thirty years, research ethics has spread across all scientific fields and strengthened its measures, criteria, and procedures on an international level. Linked to deontology and scientific integrity through its multiplying regulations, research ethics sits alongside researchers and institutions, enabling or compelling them to fulfil their responsibilities and improve citizens’ trust in science and scientists. While it aims to ensure consensus-building between all relevant stakeholders and to clarify norms of what is or should be good research, it also creates pressures and constraints that generate confusion, tensions, and even inconsistency with other norms. These norms include efficiency, acceleration, globalization, and competition, but also serendipity, freedom, and reflexivity. Analyzing discourses and practices related to research ethics brings to light the contemporary reconfiguration of the links between science and values, with research ethics emerging as a problem rather than a solution.